Daily field checking list by Walter Rosene, February 28, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated February 28, 1932. This checklist was used by Walter Rosene to record birds sighted around Beaver Creek and the Ledges. Plustek--flatbed